The effect of self-talk style on the development of academic knowledge structure of university students (Journal of the College of Basic Education, 2023)
Summary of the research:The current research aims to identify the impact of the self-talk method on developing the academic knowledge structure of university students. To achieve this, the researcher built a measure of the academic knowledge structure consisting of 14 items, and after extracting the psychometric characteristics of the scale, she applied it to a sample of 12 male and female university students divided into two groups. 6 experimental group and 6 control group, and the researcher used the appropriate statistical methods, and the scale was built, and the counseling program in the light of Meckenbaum's theory, and the results showed an effect, which means that the counseling program is successful and influential and contributed to the development of the academic knowledge structure among university students, and the researcher developed a number of Recommendations and suggestions.Keywords: psychological counseling, cognitive behavioral counseling theory, cognitive structure, self-talk